THE ROLE OF SHARIA COMPLIANCE, ISLAMIC CORPORATE GOVERNANCE AND COMPANY SIZE IN PREVENTING INTERNAL FRAUD - Desi Novita Sari; Iwan Fakhruddin; Hadi Pramono; Bima Cinintya Pratama (SEAN Institute, 2023)
This study aims to examine the effect of Sharia Compliance, Islamic Corporate Governance and Company Size on Internal Fraud in sharia banks. Independent variables used are Sharia Compliance with Profit Sharing Ratio (PSR) and Islamic Investment Ratio (IIR) as a proxy, Islamic Corporate Governance (ICG) and Company Size. The dependent variable used is Internal Fraud. The number of research samples in this study were 124 samples from total 15 Islamic banks in Indonesia that were observed during 2012–2021 using a quantitative approach. Determination of the sample obtained by using convenience sampling. This study employs Data Panel Regression with STATA 17 and were analyzed using the Fixed Effects Method. The result of this study indicate that Islamic Investment Ratio (IIR) and Company Size have positive effects on Internal Fraud. Profit Sharing Ratio (PSR) has negative effect on Internal Fraud. While Islamic Corporate Governance (ICG) has no effect on Internal Fraud.